Low-Cost Yet High-Performance Hydrochar Derived from Hydrothermal Carbonization of Duku Peel (Lansium domesticum) for Cr(VI) Removal from Aqueous Solution - Risfidian Mohadi; Novie Juleanti; Normah Normah; Patimah Mega Syah Bahar Nur Siregar; Alfan Wijaya; Neza Rahayu Palapa; Aldes Lesbani (Universitas Gadjah Mada, 2022)
Carbon-based adsorbent as a hydrochar (Hc) material with Duku (Lansium domesticum) peel precursors has been successfully synthesized as evidenced by XRD, FT-IR, BET, and SEM analysis. XRD analysis showed the presence of diffraction peaks around 16° and 22° which indicated the presence of carbonaceous material. This is confirmed by FTIR analysis which shows the presence of vibration at 2931 cm−1 of cellulose. SEM data results showed that heterogeneous and has an irregular shape and surface area increased twice from Duku peel to Hc. Duku peel and Hc adsorbent materials were applied to adsorb heavy metal ions Cr(VI). Kinetic parameters of Cr(VI) using Duku peel and Hc showed that the optimum time reached was at 120 min. The adsorption kinetics model of Cr(VI) using Hc tends to follow the PFO model and Langmuir isotherm adsorption. Duku peel material used to adsorb Cr(VI) reached an adsorption capacity of 42.19 mg/g, while in Hc material there was an increase that reached 80.64 mg/g. The thermodynamic parameters of both materials show that the adsorption process is spontaneous.